Journal of Urban Mathematics Education 2015
DOI: 10.21423/jume-v8i2a259
|View full text |Cite
|
Sign up to set email alerts
|

"I Just Wouldn't Want to Get as Deep Into It": Preservice Teachers' Beliefs about the Role of Controversial Topics in Mathematics Education

Abstract: In this article, the authors report on the initial results of a mixed methods approach to study the beliefs that preservice teachers have about teaching real-world contexts, including those related to injustices, controversial issues, and children's home and cultural backgrounds. Data collection included a survey with 92 preservice Pre-K--8 teachers, and follow-up interviews with nine survey participants. Analysis of the data suggests that preservice teachers were open to the idea of teaching mathematics throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The problem used in this study is the controversial one (Goldberg & Savenije, 2018;Mueller & Yankelewitz, 2014;Simic-Muller et al, 2015). A controversial issue is a situation that causes debate because of different points of view (Simic-Muller et al, 2015). Controversial problems arise as a result of understanding an unresolved problem, causing conflicts in one's thinking.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The problem used in this study is the controversial one (Goldberg & Savenije, 2018;Mueller & Yankelewitz, 2014;Simic-Muller et al, 2015). A controversial issue is a situation that causes debate because of different points of view (Simic-Muller et al, 2015). Controversial problems arise as a result of understanding an unresolved problem, causing conflicts in one's thinking.…”
Section: Discussionmentioning
confidence: 99%
“…In the last five years, studies on controversial mathematical problems have been carried out. Simic-Muller et al (2015), for example, conducted research on controversial reasoning in mathematics education. Mueller and Yankelewitz (2014) revealed that controversial issues lead to many different reasons.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations